Seeing Chekhov : life and art - Finke, Michael C., 1957- (Cornell University Press, 2005)
"Michael C. Finke explodes a century of critical truisms concerning Chekhov's objective eye and what being a physician gave him as a writer in a book that foregrounds the deeply subjective and self-reflexive aspects of his fiction and drama. In exploring previously unrecognized seams between the author's life and his verbal art, Finke profoundly alters and deepens our understanding of Chekhov's personality and behaviors, provides new interpretations of a broad array of Chekhov's texts, and fleshes out Chekhov's simultaneous pride in his identity as a physician and devastating critique of turn-of-the-century medical practices and ideologies." "Seeing Chekhov is essential reading for students of Russian literature, devotees of the short story and modern drama, and anyone interested in the intersection of literature, psychology, and medicine."--Jacket